(untitled) (Applied Biological Research, 2018)
Genetic diversity analysis of yield and yield contributing traits in F2 population of wheat cross ‘Kharchia 65 x HD 2851’ wasestimated, based on D2-statistics, for 100 selected phenotypically superior plants that were grouped into 13 clusters. Clustering pattern revealedthat cluster II and IV were the largest ones with 14 genotypes. The highest inter-cluster distance was observed between clusters VII and VIII (11.67), followed by between clusters VII and X (10.85), VII and IX (9.88) and VII and XII (9.88). This indicates that plants included in these clusters possess wide genetic diversity. Further, cluster VIII exhibited high mean value for number of spikelets spike-1 (18.0), number of grains ear-1 (36.0), grain yield plant-1 (0.911 g) and biological yield plant-1 (4.342 g). Cluster I showed highest mean value for the number of grains spikelet-1(3.0), moderate 1000-grain weight (32.95 g) and acceptable harvest index (34.6%). The clusters VII, I, II, III, XI and XII were outstanding on the basis of better cluster mean for most of the characters. The genotypes in these clusters should be selected and utilized to the advanced generation in a breeding program for improved salinity tolerance.